2017
DOI: 10.7575/aiac.ijalel.v.6n.2p.127
|View full text |Cite
|
Sign up to set email alerts
|

Changes in University Students’ Perceptions towards a Two-Week Summer English Immersion Program

Abstract: The present research examined how university students perceived a 2-week summer English immersion program organized and designated by Chinese teachers of English in a highly prestigious university in Beijing and whether their perceptions changed during the period. Data included 208 surveys and 19 informal interviews in week 1 and 207 surveys and 19 interviews in week 2 (the participants were largely the same in both weeks). Analyses of the data showed that in both weeks, most students considered the courses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…(2008) investigated 534 Hispanic English learners from 28 elementary schools in the USA claimed that English immersion program helped students develop their oral proficiency effectively. At university level, Liu, Hu, and Peng (2017) investigated how 208 Chinese students perceived a two-week English immersion programme. The results of the study show that in both weeks, the majority of students found the courses interesting and liked the majority of them for similar reasons (e.g., being interesting and having a lot of participation), that the program improved students' English abilities in listening, speaking, reading, and writing as well as overall English proficiency, and that the program improved students' interpersonal communication ability, confidence in using English, and knowledge of the culture of English.…”
Section: Introductionmentioning
confidence: 99%
“…(2008) investigated 534 Hispanic English learners from 28 elementary schools in the USA claimed that English immersion program helped students develop their oral proficiency effectively. At university level, Liu, Hu, and Peng (2017) investigated how 208 Chinese students perceived a two-week English immersion programme. The results of the study show that in both weeks, the majority of students found the courses interesting and liked the majority of them for similar reasons (e.g., being interesting and having a lot of participation), that the program improved students' English abilities in listening, speaking, reading, and writing as well as overall English proficiency, and that the program improved students' interpersonal communication ability, confidence in using English, and knowledge of the culture of English.…”
Section: Introductionmentioning
confidence: 99%